2015
DOI: 10.1038/cddis.2015.297
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-22 inhibits tumor growth and metastasis in gastric cancer by directly targeting MMP14 and Snail

Abstract: MicroRNAs (miRNAs) deregulation is frequent in human gastric cancers (GCs), but the role of specific miRNAs involved in this disease remains elusive. MiR-22 was previously reported to act as tumor suppressors or oncogenes in diverse cancers. However, their accurate expression, function and mechanism in GC are largely unclear. Here, we found that the expression of miR-22 was significantly reduced in clinical GC tissues compared with paired adjacent normal tissues, and was significantly correlated with a more ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 44 publications
6
90
0
Order By: Relevance
“…MiR-22 is located at chromosomal region 17p13.3 [10]. MiR-22 has been shown to be a tumor suppressor in metastatic breast cancer and gastric cancers [11, 12]. Interestingly, miR-22 expression has been found to be decreased in patients with coronary artery disease (CAD) and diseases displaying an inflammatory response [13].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-22 is located at chromosomal region 17p13.3 [10]. MiR-22 has been shown to be a tumor suppressor in metastatic breast cancer and gastric cancers [11, 12]. Interestingly, miR-22 expression has been found to be decreased in patients with coronary artery disease (CAD) and diseases displaying an inflammatory response [13].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-22 has been determined to be a regulator or an inhibitor in diverse cancers, including osteosarcoma, prostate cancer, cervical cancer, lung cancer, [44]breast cancer[45], colorectal cancer[46], gastric cancer [47, 48], ovarian cancer[49], acute myeloid leukemia[50], medulloblastomas[51], endometrial endometrioid carcinomas[52], esophageal squamous cell carcinoma[53] and hepatocellular carcinoma[54]. The study by Zhou et al [55] found that miR-22 is downregulated in HCC and that its expression is associated with the differentiation, metastasis and prognosis of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that aberrantly expressed miRNAs play essential roles in tumorigenesis and progression processes [9]. Recently, it has been reported that miR-940, miR-363, miR-25, and miR-269-5p function as oncogenes in gastric cancer [1012], whereas miR-22, and miR-361-5p function as tumor suppress genes [1315]. …”
Section: Introductionmentioning
confidence: 99%